2004
DOI: 10.1016/j.pain.2004.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species (ROS) play an important role in a rat model of neuropathic pain

Abstract: Reactive oxygen species (ROS) are free radicals produced in biological systems that are involved in various degenerative brain diseases. The present study tests the hypothesis that ROS also play an important role in neuropathic pain. In the rat spinal nerve ligation (SNL) model of neuropathic pain, mechanical allodynia develops fully 3 days after nerve ligation and persists for many weeks. Systemic injection of a ROS scavenger, phenyl-N-tert-butylnitrone (PBN), relieves SNL-induced mechanical allodynia in a do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
314
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 404 publications
(330 citation statements)
references
References 41 publications
12
314
1
3
Order By: Relevance
“…Kim et al 5 showed that reactive oxygen species (ROS) play a role in neuropathic pain mediation, and they also showed that the use of ROS scavengers ameliorated the mechanical discomfort in a single nerve ligation pain model in rats. Thus, vitamin C may play a role in antinociception through its antioxidative properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al 5 showed that reactive oxygen species (ROS) play a role in neuropathic pain mediation, and they also showed that the use of ROS scavengers ameliorated the mechanical discomfort in a single nerve ligation pain model in rats. Thus, vitamin C may play a role in antinociception through its antioxidative properties.…”
Section: Discussionmentioning
confidence: 99%
“…3 Vitamin C is also known for its antioxidant, neuroprotective, and neuromodulating effects. [3][4][5][6][7] Clinical studies have shown that oral supplementation of vitamin C in the range of 0.5-3 g might play a role in pain treatment without any significant side effects. In a double-blind placebo-controlled crossover study, Jensen et al 8 have shown that 1 g of vitamin C reduced pain and improved function in patients with hip and knee osteoarthritis.…”
Section: Résumémentioning
confidence: 99%
“…Reactive oxygen species (ROS) are known to cause persistent pain (40)(41)(42)(43)(44) C111 C164 C239 C264 C269 C369 C393 C397 C540 C586 C624 C641 C722 C748 C772 C783 are indiscriminative (45), compromising multiple cell types to exacerbate tissue inflammation and nociception. Although a significant part of hyperalgesia can arise from action of ROS on the spinal cord (44,46), sensory transduction channels in peripheral nerves may also contribute to pain related to oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found in numerous studies that reactive oxygen species (ROS) cause nerve injury-related pain and inflammatory pain (7). Paclitaxel has also been reported to activate proinflammatory cytokine expression (8)(9)(10)(11).…”
mentioning
confidence: 99%